2021
DOI: 10.2174/1567205018666211022091110
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Probiotic Formula, BIOCG, Protects Against Alzheimer’s-Related Cognitive Deficits via Regulation of Dendritic Spine Dynamics

Abstract: Background: The brain-gut-microbiome axis has emerged as an important pathway through which perturbations in the gut and/or microbial microenvironment can impact neurological function. Such alterations have been implicated in a variety of neuropsychiatric disorders, includ- ing depression, anxiety, and Alzheimer’s Disease (AD) and the use of probiotics as therapy for th- ese diseases remains promising. However, the mechanisms underlying the gut microenvironment’s influence on disease pathogenesis and therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…In support of these findings, we observed higher transcript levels of NSMF, a regulator of the DNA repair response ( Ju et al, 2021 ), and BDNF that is involved in neuronal survival in the whole brain extracts of the mice receiving Lab4b to the Control group. A recent study of Sun M. et al (2021) demonstrated the ability of another probiotic to increase spine densities in the cortex of 3xTg-AD mice. Our own studies have also shown beneficial effects of probiotics on neuronal health in vitro with Lab4b demonstrating an ability to prevent loss of viability in human SH-SY5Y neurones exposed to neurotoxic challenge ( Michael et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of these findings, we observed higher transcript levels of NSMF, a regulator of the DNA repair response ( Ju et al, 2021 ), and BDNF that is involved in neuronal survival in the whole brain extracts of the mice receiving Lab4b to the Control group. A recent study of Sun M. et al (2021) demonstrated the ability of another probiotic to increase spine densities in the cortex of 3xTg-AD mice. Our own studies have also shown beneficial effects of probiotics on neuronal health in vitro with Lab4b demonstrating an ability to prevent loss of viability in human SH-SY5Y neurones exposed to neurotoxic challenge ( Michael et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a substantial number of such studies are needed to support and confirm such observations (Mazraeh et al, 2019). Probiotics are the existing microorganisms in our gut that play a role to healthy status (Sun et al, 2021). Such microbes could be found in fermented foods like yogurt, sauerkraut, and many more (Rezac et al, 2018).…”
Section: Nutrition and Cancer Treatmentmentioning
confidence: 99%